Case study of student participation in transition program: Literature review - Nurfahmi, Alfi; Nur Azizah (Caraka Olah Pikir Edukatif, 2025)
Transition programs for students with disabilities are an effort to prepare students from school to post-school life. According to the Individuals with Disabilities Education Improvement Act (IDEA), transition services must be coordinated, outcome-oriented, and tailored to individual student needs. Taxonomy for Transition Programming 2.0 emphasizes five key areas, including student-focused planning, self-determination development, and student participation in developing an IEP. This study aims to explore the role of students with disabilities in transition programs through a literature review. The method employed was a Systematic Literature Review (SLR) with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The literature search was conducted through the ERIC, Google Scholar, ScienceDirect, and Sage Journals databases. The results show that student participation in transition programs varies, with students with severe intellectual disabilities tending to have lower participation rates. Factors such as functional skills, communication, and environmental support influence student engagement